Spillover Effects or Endowment Factors Caused Regional Inequality in Gresik District? - Gigih Prihantono; Herlina Eka Subandriyo Putri; Oldheva Genisa Sabilau (East Java Economic Journal, 2022)
Gresik Regency is one of the centers of growth in East Java Province. With a location agglomeration area in East Java Province, it is not surprising that Gresik Regency gets an economic spillover (spillover effect) from the City of Surabaya. The spillover effect is an impact that arises because of the dependence relationship between the growth poles and the surrounding area. The main method in this research is use econometric models. The unit of observation of this study includes the dependent variable, namely regional disparity as measured by the Williamson Index, and independent variables, namely factors that theoretically affect regional disparities. The unit of analysis in this study includes 18 (eighteen) sub-districts in Gresik Regency. The areas with a high disparity level (IW value 50<) are located in areas bordering the city of Surabaya, such as Gresik istrict, Kebomas District, Cerme District, Menganti District and Driyorejo District. The study prove that the impact factor regional spillover has an significantimpact on the overall regional development.